Modulating the valence of Ga and the deep level impurity for high thermoelectric performance of n-type Pb0.98Ga0.02Te1-xSex compounds. (October 2022) - Shi, Y.; Tang, Y.; Liu, K.; Zhong, S.; Chen, S.; Yu, L.; Wu, J.; Zhang, Q.; Su, X.; Tang, X.
Abstract: It has been found that the doped Ga has a distinct role in PbTe and PbSe compounds though they possess the same crystal structure. Therefore, to understand how the thermoelectric performance evolves in the Ga-doped PbTe1-x Sex solid solution is crucial. Herein, we report that a maximum ZT value of 1.57 at 721 K and a high average ZT value of 1.13 in the temperature range of 300–843 K are attained for Pb0.98 Ga0.02 Te0.96 Se0.04 compound. The experimental studies show that doping Ga into PbTe introduces a shallow level impurity state Ga 3+ and a deep level associated with the Ga  +  state simultaneously. Interestingly, upon Se-alloying all of the Ga  +  are oxidized into Ga 3+ at low temperatures, which increases the room-temperature carrier concentration from 1.16 × 10 19  cm −3 to 2.17 × 10 19  cm −3 . This leads to an improved power factor of 3.04 mW m −1  K −2 for Pb0.98 Ga0.02 Te0.96 Se0.04 sample at 482 K. Additionally, Se-alloying further enhances the point defect phonon scattering and lowers the lattice thermal conductivity to 0.46 W m −1  K −1 for Pb0.98 Ga0.02 Te0.96 Se0.04 sample at 690 K. As a result, the ZT value is increased by about 112% compared with the maximum ZT of 0.74 for pristine PbTe. This work provides a new avenue for tuning the doping behavior of cation site dopant via alloying on anion site to further improve the ZT value in thermoelectric materials. Graphical abstract: Image 1 Highlights: Ga + is oxidized into Ga 3+ upon Se alloying in Pb0.98 Ga0.02 Te1-x Sex compounds and thereby increasing the carrier concentration. Ga/Se co-doping enhances point defect phonon scattering. Remarkable ZT max of 1.57 and ZT avg of 1.13 are achieved in Pb0.98 Ga0.02 Te0.96 Se0.04 compound.